Effect of processing on the microstructure and induced-strain mismatch in magnesia-alumina-layered composites - Kim, Chang Soo; Lombardo, Stephen J.; Winholtz, Robert A. (BLACKWELL PUBLISHING, 2006)
A method is described whereby thin ceramic shapes are induced to adopt a different shape at elevated temperature without the application of an external pressure. To achieve deformation, thin beams of alumina are coated with magnesia; at a high temperature, the strain mismatch that arises in the sample leads to deformation. Scanning electron microscopy and compositional profiling suggest that a bilayer structure forms. One layer contains both Mg and Al cations and the spinel phase is present, whereas the second layer consists predominantly of alumina. A mechanics model based on strain mismatch in bilayer systems indicates how the resulting curvature depends on the thickness of the two regions. A mechanistic model is derived that describes the strain mismatch in terms of the degree of conversion to spinel, the amount of differential sintering between layers, and the amount of residual porosity present in the two layers of the substrate.
Keywords: CONSTRAINED DENSIFICATION; EXTERNAL-PRESSURE; SYSTEM MGO-AL2O3; SOLID-STATE; THIN-FILMS; SPINEL; DEFORMATION; ACTUATORS; CURVATURE; CERAMICS